The Analysis of Heat Transfer on Hot Air Coffee Roasters at the Appropriate Technology Research Centre, National Research and Innovation Agency in Subang - Susilawati Susilawati; Azhis Sholeh Buchori; Nurizzi Rifqi Ferdian; Dimas Rizky Ummaramdani; Dadang Hidayat; Oyok Yudiyanto; Faadiyah Cheryl Rhacelia (Universitas Sultan Ageng Tirtayasa, 2023)
Roasting occurs due to heat transfer from the heating surface into the material. Coffee roasting plays an important role in determining the chemical composition, aroma, and taste of coffee. There are two main types of coffee roasters, namely drum and hot air roasters. This research aims to determine the heat transfer in hot air coffee roasters. The data collected consists of roasting time, coffee bean temperature, roasting room temperature, fuel consumption and air flow speed in the cyclone system chimney and sample was carried out at medium roasting level, with three repetitions. The method used is theoretical analysis and experimental testing. The results showed that the heat transfer mechanism in hot air roasting is a conduction and convection mechanism. The amount of conduction and convection heat transfer in the coffee roasting equipment was carried out in three repetitions. It was also found that factors that influence the rate of heat transfer in hot air roasting equipment are due to conduction and convection, as well as influenced by heat transfer surface area, thermal conductivity, air flow speed from blower pressure and pressure on the gas fuel. The results of the research show that the heat transfer mechanism in hot air roasting is a conduction and convection mechanism. The amount of heat transfer in one repetition of the conduction quantity (Q) is 9222.8 W and the convection rate (Q) is 3209.4 W with an average efficiency of 34.7%, in two repetitions the conduction quantity (Q) is 9883.3 W and the convection rate (Q) is 3444.6 W with the average efficiency is 34.8%, at three repetitions the conduction (Q) is 9690.3 W and the convection rate (Q) is 1123.3 W, the average efficiency is 11.6%. Factors that influence the rate of heat transfer in hot air roasting tools are conduction and convection, heat transfer surface area, thermal conductivity, air flow speed due to blower pressure and pressure on LPG gas fuel.